Peran financial technology sebagai inovasi keuangan digital pada perbankan syariah di era society 5.0 - Wahyudi, Muhammad Arifky (Maliki Interdisciplinary Journal, 2025)
This article discusses the role of financial technology (fintech) as a digital finance innovation in Islamic banking during the Society 5.0 era. With advancements in digital technology, Islamic banking faces significant opportunities and challenges. Fintech has revolutionized Islamic banking services through mobile banking applications, peer-to-peer lending platforms, and blockchain technology, enabling broader access for customers, especially the younger generation. This innovation not only enhances operational efficiency but also strengthens financial inclusion by facilitating transactions. However, challenges such as data security and compliance with Sharia principles must still be addressed. The article also highlights the importance of digital literacy and flexible regulations to support the development of fintech in Islamic banking. Thus, the collaboration between technology and Sharia principles is key to creating a more inclusive and sustainable financial ecosystem